Health service engagement, side effects and concerns among men with anabolic-androgenic steroid use: a cross-sectional Norwegian study - Hans Christian Bordado Henriksen; Ingrid Amalia Havnes; Marie Lindvik Jørstad; Astrid Bjørnebekk (Substance Abuse Treatment, Prevention, and Policy, 2023)
Abstract Background Recreational use of anabolic-androgenic steroids (AAS) is a public health concern world-wide associated with a range of physical and psychological side effects. Still, people who use AAS tend to be reluctant to seek treatment. This study aims to explore use characteristics, treatment-seeking behaviour, side effects and associated health concerns among men with AAS use. Methods The study includes cross-sectional self-report data from 90 men with a current or previous use of AAS exceeding 12 months, where 41 (45.6%) had sought treatment at least once during their lifetime, and 49 (54.4%) had not. Health service engagement was examined with descriptive statistics on reasons for contacting health services, transparency about AAS use, satisfaction with health services and reasons for not seeking treatment. Furthermore, experienced side effects and health concerns were compared between the treatment seeking and the non-treatment seeking group, using two-sample t-tests and Chi2 or Fisher exact tests for numerical and categorical variables, respectively. Results All 90 AAS-using men reported side effects from AAS use. Treatment seekers were significantly younger, experienced more side effects including gynecomastia, excessive sweating, fatigue, depression and anxiety, and expressed more concern for testosterone deficiency. Preventive health check-up was the most common reason for seeking treatment (n = 22, 53.7%), and 38 men (93%) were transparent about AAS use during consultations with health professionals. The main reported reasons for not seeking healthcare services were that the experienced side effects were not considered to be of treatment demanding nature (n = 39, 79.6%) and the belief that healthcare providers had scarce knowledge about AAS use and its health impacts (n = 12, 24.5%). Conclusions Reluctance to seek treatment among people who use AAS, despite having associated side effects and health concerns, may contribute to continued health risks. It is important to fill the knowledge gap on how to reach and treat this new patient group, and policy makers and treatment providers need to be educated on how to meet their treatment needs.